Legal Aspects of the Safety of Healthcare Professionals Working with Migrants - Brito, Dalila; Vilela, Idalina; Bessa Vilela, Noemia (Medicine, Law & Society, 2017)
The coexistence of multiple cultures is a challenge that requires behavioral changes for the health professionals, in particular nurses. This work’s objective was to understand the factors and beliefs that influence the demand for health care from immigrants in the Porto metropolitan area (Portugal), and their accessibility to the health services. We developed an exploratory-descriptive qualitative study. We obtained the data through semi-structured interviews of eleven Ukrainian residents of the Porto metropolitan area. We used the twelve cultural domains of Purnell. Sampling was non-probability, of convenience and in “snowball”. Participants were required to give their free and informed consent. The results indicated some difficulties accessing health care due to inefficient communication, resulting from the language barrier and/or of different interpretations, and the disarticulation between the different immigrant support services. This study allowed the implementation of strategies designed to promote health care directed to immigrants, taking into consideration the diversity and vulnerability when accessing health services.